2016
DOI: 10.1177/0731684415624768
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of temperature distribution in an autoclave

Abstract: In this work, the temperature distribution on an industrial mold tool is monitored during autoclave runs with three settings. In one of the settings, the temperature and pressure follow a scheme used in real moldings, while in the other two cases, the temperature is increased as fast as possible with and without an applied pressure. The temperature difference over the tool is relatively large and varies between 29 C and 76 C validating a detailed investigation of the temperature at different points. Two result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 21 publications
2
45
0
Order By: Relevance
“…The conventional composite curing in this study was conducted with an autoclave, comprising a vacuum bag and applied pressure of 0.7 MPa, following the manufacturer's recommended cure cycle . A hot‐plate was utilized instead of a heating vessel (e.g., oven) for composite curing without an applied pressure (i.e., vacuum‐only curing), in order to avoid spatial gradients in cure due to uncertainty of convective‐to‐conductive interactions between the convective medium and cure materials . In the case of OoO curing, vacuum was applied via a vacuum bag without an applied pressure as the OoO curing is originally designed .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The conventional composite curing in this study was conducted with an autoclave, comprising a vacuum bag and applied pressure of 0.7 MPa, following the manufacturer's recommended cure cycle . A hot‐plate was utilized instead of a heating vessel (e.g., oven) for composite curing without an applied pressure (i.e., vacuum‐only curing), in order to avoid spatial gradients in cure due to uncertainty of convective‐to‐conductive interactions between the convective medium and cure materials . In the case of OoO curing, vacuum was applied via a vacuum bag without an applied pressure as the OoO curing is originally designed .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, even the use of OoA prepregs is not completely ideal from a manufacturing point of view. Heat transfer is still based on convection, which leads to inefficiencies and to spatial gradients in cure and stress due to convective‐to‐conductive interactions between the oven gas medium (usually air) and the cure materials . This method drives part‐to‐part variability, and the fabrication is still limited because of the fixed geometry of the heating vessel.…”
Section: Introductionmentioning
confidence: 99%
“…At the higher temperatures (over 200 C) involved in thermoplastics processing, radiation is usually an important heat transfer mode in autoclave process. 20 However, as the temperatures typically used in the fabrication of thermoset composite materials is usually less than 200 C, forced convection is undoubtedly the major heat transfer process between parts and tooling and the surrounding gases inside an autoclave, 26 and the effect of radiation is considered unremarkable. [21][22][23][24][25] Therefore, the temperature distribution in an autoclave is mainly determined by the heat convection in fluid regions and heat conduction in solid regions.…”
Section: Modeling Of the Autoclave Process Typical Structure Of An Autoclavementioning
confidence: 99%
“…From a thermal point of view, HTC between air and mold in different areas of the mold was determined by shift factors in Weber et al's 25 study. Moreover, an experimental study and numerical simulation were conducted by Kluge et al 19,26 to discuss the temperature distribution of a mold in the autoclave. Comparing with previous studies, the mold used in Kluge's research has a more complex shape, which contributed much to the turbulence of flow.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [ 23 ] conducted a simulation of mold in the autoclave, which focused on the study of boundary layer grids to make the simulation results more accurate. Kluge et al [ 24 ] investigated the temperature distribution in the industrial mold in an autoclave. The results indicated that positions on the upstream side of the tool are heated faster than the downstream positions.…”
Section: Introductionmentioning
confidence: 99%